Public Private Partnership in Urban Rail Systems Model Concession Agreement January 2009 - Planning Commission (Planning Commission, 2009)
The last fifty years have witnessed an explosive growth in urbanisation and has generated considerable pressure on urban infrastructure causing traffic congestion, pollution and high transport costs. Public transport systems have not been able to keep pace with the growth in traffic leading to loss of productive time, increased costs and higher pollution levels. It is, therefore, essential to promote public transport with a view to easing congestion and improving the quality of life. In the developed world, metro rail systems are the fastest and the cheapest mode of public transport.
Planning Commission Government Of India
Planning Commission Government of India